Outcome of acute leukemia patients with central nervous system (CNS) involvement treated with total body or CNS irradiation before transplantation - Kuo, Wen-Han; Chen, Yu-Hsuan; Tsai, Cheng-Hong; Liao, Xiu-Wen; Kuo, Sung-Hsin; Tang, Jih-Luh (Therapeutic Radiology and Oncology, 2018)
Background: Central nervous system (CNS) involvement is a poor prognostic factor for patients with acute leukemia. Currently, there is still no standard approach to effectively reduce the CNS relapse rate and improve outcome. The purpose of the study was to evaluate whether radiation therapy (RT) at pre-transplantation setting with either total body irradiation (TBI) for conditioning or CNS-directed RT would improve CNS relapse rate or survival after transplantation. Methods: We retrospectively reviewed the database in NTUH stem cell transplantation center from 1995 to 2016 and included consecutive acute myeloid and lymphoblastic leukemia patients with CNS disease before transplantation. CNS involvement was mandatory, either at initial presentation or relapse before transplantation. A total of 55 patients were included. All patients received allogeneic transplantation, and most of them received myeloablative conditioning. Overall survival (OS), relapse-free survival (RFS), and 2-year CNS RFS after transplantation were compared between patients with RT and without RT using Kaplan-Meier analysis. Results: The 2-year OS was 72.5% for patients with RT, and 72.2% without RT (log-rank test, P=0.111). The 2-year RFS was 69.4% for patients with RT, and 44.4% without RT (P=0.164). The 2-year post-transplantation CNS RFS was 73.3% for patients with RT, and 74.1% without RT (P=0.742). Multivariate analysis revealed that pre-transplantation disease status (with complete response, P=0.03) and TBI or CNS RT (P=0.04) were significantly associated with better OS rate. TBI or CNS RT (P=0.03) was also independently associated with improved RFS, but had only marginally significant impact on CNS RFS (P=0.068). Conclusions: Our study has shown that there was potential OS and RFS benefit of peri-transplantation radiation, including TBI conditioning or CNS RT, for acute leukemia patients with CNS involvement.